Changing macroeconomic dynamics at the zero lower bound - Zanetti, F; Liu, P; Mumtaz, H; Theodoridis, K (University of Oxford, 2017)
This paper develops a change-point VAR model that isolates four major macroeconomic regimes in the US since the 1960s. The model identi es shocks to demand, supply, monetarypolicy, and spread yield using restrictions from a general equilibrium model. The analysis discloses important changes to the statistical properties of key macroeconomic variables and their responses to the identi ed shocks. During the crisis period, spread shocks became more important for movements in unemployment and in ation. A counterfactual exercise evaluates the importance of lower bond-yield spread during the crises and suggests that the Fed's largescale asset purchases helped lower the unemployment rate by about 0.6 percentage points, while boosting in ation by about 1 percentage point.